Solve for a_1 (complex solution)
\left\{\begin{matrix}a_{1}=-\frac{2b_{1}x+c_{1}}{x^{2}}\text{, }&x\neq 0\\a_{1}\in \mathrm{C}\text{, }&c_{1}=0\text{ and }x=0\end{matrix}\right.
Solve for b_1 (complex solution)
\left\{\begin{matrix}b_{1}=-\frac{a_{1}x^{2}+c_{1}}{2x}\text{, }&x\neq 0\\b_{1}\in \mathrm{C}\text{, }&c_{1}=0\text{ and }x=0\end{matrix}\right.
Solve for a_1
\left\{\begin{matrix}a_{1}=-\frac{2b_{1}x+c_{1}}{x^{2}}\text{, }&x\neq 0\\a_{1}\in \mathrm{R}\text{, }&c_{1}=0\text{ and }x=0\end{matrix}\right.
Solve for b_1
\left\{\begin{matrix}b_{1}=-\frac{a_{1}x^{2}+c_{1}}{2x}\text{, }&x\neq 0\\b_{1}\in \mathrm{R}\text{, }&c_{1}=0\text{ and }x=0\end{matrix}\right.
Graph
Share
Copied to clipboard
a_{1}x^{2}+c_{1}=-2b_{1}x
Subtract 2b_{1}x from both sides. Anything subtracted from zero gives its negation.
a_{1}x^{2}=-2b_{1}x-c_{1}
Subtract c_{1} from both sides.
x^{2}a_{1}=-2b_{1}x-c_{1}
The equation is in standard form.
\frac{x^{2}a_{1}}{x^{2}}=\frac{-2b_{1}x-c_{1}}{x^{2}}
Divide both sides by x^{2}.
a_{1}=\frac{-2b_{1}x-c_{1}}{x^{2}}
Dividing by x^{2} undoes the multiplication by x^{2}.
a_{1}=-\frac{2b_{1}x+c_{1}}{x^{2}}
Divide -2b_{1}x-c_{1} by x^{2}.
2b_{1}x+c_{1}=-a_{1}x^{2}
Subtract a_{1}x^{2} from both sides. Anything subtracted from zero gives its negation.
2b_{1}x=-a_{1}x^{2}-c_{1}
Subtract c_{1} from both sides.
2xb_{1}=-a_{1}x^{2}-c_{1}
The equation is in standard form.
\frac{2xb_{1}}{2x}=\frac{-a_{1}x^{2}-c_{1}}{2x}
Divide both sides by 2x.
b_{1}=\frac{-a_{1}x^{2}-c_{1}}{2x}
Dividing by 2x undoes the multiplication by 2x.
b_{1}=-\frac{a_{1}x}{2}-\frac{c_{1}}{2x}
Divide -a_{1}x^{2}-c_{1} by 2x.
a_{1}x^{2}+c_{1}=-2b_{1}x
Subtract 2b_{1}x from both sides. Anything subtracted from zero gives its negation.
a_{1}x^{2}=-2b_{1}x-c_{1}
Subtract c_{1} from both sides.
x^{2}a_{1}=-2b_{1}x-c_{1}
The equation is in standard form.
\frac{x^{2}a_{1}}{x^{2}}=\frac{-2b_{1}x-c_{1}}{x^{2}}
Divide both sides by x^{2}.
a_{1}=\frac{-2b_{1}x-c_{1}}{x^{2}}
Dividing by x^{2} undoes the multiplication by x^{2}.
a_{1}=-\frac{2b_{1}x+c_{1}}{x^{2}}
Divide -2b_{1}x-c_{1} by x^{2}.
2b_{1}x+c_{1}=-a_{1}x^{2}
Subtract a_{1}x^{2} from both sides. Anything subtracted from zero gives its negation.
2b_{1}x=-a_{1}x^{2}-c_{1}
Subtract c_{1} from both sides.
2xb_{1}=-a_{1}x^{2}-c_{1}
The equation is in standard form.
\frac{2xb_{1}}{2x}=\frac{-a_{1}x^{2}-c_{1}}{2x}
Divide both sides by 2x.
b_{1}=\frac{-a_{1}x^{2}-c_{1}}{2x}
Dividing by 2x undoes the multiplication by 2x.
b_{1}=-\frac{a_{1}x}{2}-\frac{c_{1}}{2x}
Divide -a_{1}x^{2}-c_{1} by 2x.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}